Abuse, misuse, and suicidal substance use by children on school property. (21st October 2015) - Vakkalanka, J. Priyanka; King, Joshua D.; Holstege, Christopher P.
Abstract : Objective. The purpose of this study was to characterize the epidemiological trends associated with substances used in intentional exposures among children while on school property reported to the U.S. National Poison Data System (NPDS). Materials and Methods . NPDS was queried for intentional (abuse, misuse, suspected suicide, and unknown intentional) exposures reported to occur on school property between calendar years 2004 and 2013. Records were restricted to children 6–18 years of age. Demographic, exposure, and clinical characteristics were assessed. Results . A total of 56, 882 substances were intentionally used on school property by 50, 379 children, of which 39.8% were females ( n = 20, 070), 57.7% were males ( n = 29, 084), and 2.4% were unknown gender ( n = 1, 225). The most frequent pharmaceutical exposures reported included sedatives ( n = 4, 096; 8.1%), analgesics ( n = 4, 022; 8.0%), and cough and cold preparations ( n = 3, 529; 7.0%). The majority of exposures were managed on site ( n = 21, 464; 42.6%), followed by care at a healthcare facility ( n = 20, 048; 39.7%). Serious outcomes (moderate or major effects and death) accounted for nine percent of all reported exposures. Compared to reference groups, female gender, teenagers 17–18 years, and pharmaceutical substances (Prevalence Ratios = 4.6, 9.4, and 9.9, respectively) were associated with suspected suicides when compared with other intentional exposures. Conclusions . Along with other national data about behaviors in the adolescent and teenage population, additional trends in risky behavior may be gleaned by surveillance through poison centers. With over 5, 000 annual reports to the poison centers about intentional exposures on school property, school personnel and parents/guardians must be vigilant about the range of pharmaceutical and non-pharmaceutical substances that are used for abuse, misuse, or suicide.